Screen style: Visual elements and brand identity in fashion films - Lopes, M. M.; Damásio, M. J.; Sousa, C.; Rodrigues, H. (Journal of Marketing Communications)
This study examines how fashion films are perceived by different audience segments, with a focus on two primary visual elements: costume and cinematography. Using an experimental and segmentation-based approach, the study assesses how these elements influence the perception of brand identity. A sample of 318 participants, segmented by their relationship with fashion, were shown a fashion film and then completed a structured questionnaire. The results show that fashion professionals and students consistently value these visual elements more than ordinary consumers, and that their perception is positively associated with the effectiveness of brand communication. The findings highlight the symbolic power of costume and cinematography in constructing aesthetic, emotional, and cultural meanings. From a strategic perspective, the study suggests that fashion films can be highly effective tools for communicating brand identity, particularly when targeting more fashion-savvy audiences. This research contributes to a better understanding of how fashion films function as symbolic and immersive branding experiences.